Possible Role of Myopia as a Risk Factor for Mechanical Neck Pain in Medical Students: A Pilot Study: - Kardeh, Bahareh; Ashraf, Alireza; Kardeh, Sina (Galen Medical Journal, 2019)
Background: Mechanical neck pain (MNP) is a common health concern. Some studies suggested a relationship between neck pain and visual activity. We assessed the role of myopia as a contributing factor in the development of chronic MNP. Materials and Methods: All medical students at Shiraz University School of Medicine, who were 18 to 22 years old, were invited to participate in this retrospective case-control study from March 2016 to March 2017. Numeric Pain Rating Scale (NPRS) was used to assess the average neck pain severity over the past 6 months in order to enroll participants as the case (â‰¥3) or control (<3) groups. Demographic data and medical profile were obtained. After identifying eligible cases, we assigned age- and sex-matched controls, who also met the study criteria. Subsequently, participants completed the Neck Disability Index (NDI) and Neck Pain and Disability Scale (NPDS) questionnaires and were evaluated for myopia severity. Variables were compared between the case and control groups as well as within the case group. P-value<0.05 was considered statistically significant.Â Results: From over 700 medical students, around 150 cooperated. Eventually, 31 eligible cases (and 31 controls) were studied. NDI and NPDS were significantly higher in the case group (P<0.001). However, no significant differences were noticed between the groups regarding the severity (P=0.123) and the duration (P=0.417) of myopia. Also, the correlation of myopia severity with NDPS (Ï=0.159, P=0.216) and NDI (Ï=0.201, P=0.116) was non-significant within the case group.Â Conclusion: Our findings have not supported the influential role of myopia in the development of chronic MNP.Â  [GMJ.2019;8:e1287]